Diesel exhaust particles alter mitochondrial bioenergetics and cAMP producing capacity in human bronchial epithelial cells - Cattani-Cavalieri, Isabella; Trombetta-Lima, Marina; Yan, Hong; Manzano-Covarrubias, Ana L.; Baarsma, Hoeke A.; Oun, Asmaa; van der Veen, Melissa Mol; Oosterhout, Emily; Dolga, Amalia M.; Ostrom, Rennolds S.; Valenca, Samuel Santos; Schmidt, Martina (Frontiers in Toxicology, 2024)
Introduction: Air pollution from diesel combustion is linked in part to the generation of diesel exhaust particles (DEP). DEP exposure induces various processes, including inflammation and oxidative stress, which ultimately contribute to a decline in lung function. Cyclic AMP (cAMP) signaling is critical for lung homeostasis. The impact of DEP on cAMP signaling is largely unknown.Methods: We exposed human bronchial epithelial (BEAS-2B) cells to DEP for 24–72 h and evaluated mitochondrial bioenergetics, markers of oxidative stress and inflammation and the components of cAMP signaling. Mitochondrial bioenergetics was measured at 72 h to capture the potential and accumulative effects of prolonged DEP exposure on mitochondrial function.Results: DEP profoundly altered mitochondrial morphology and network integrity, reduced both basal and ATP-linked respiration as well as the glycolytic capacity of mitochondria. DEP exposure increased gene expression of oxidative stress and inflammation markers such as interleukin-8 and interleukin-6. DEP significantly affected mRNA levels of exchange protein directly activated by cAMP-1 and -2 (Epac1, Epac2), appeared to increase Epac1 protein, but left phospho-PKA levels unhanged. DEP exposure increased A-kinase anchoring protein 1, β2‐adrenoceptor and prostanoid E receptor subtype 4 mRNA levels. Interestingly, DEP decreased mRNA levels of adenylyl cyclase 9 and reduced cAMP levels stimulated by forskolin (AC activator), fenoterol (β2-AR agonist) or PGE2 (EPR agonist).Discussion: Our findings suggest that DEP induces mitochondrial dysfunction, a process accompanied by oxidative stress and inflammation, and broadly dampens cAMP signaling. These epithelial responses may contribute to lung dysfunction induced by air pollution exposure.